STUDI PENGGUNAAN ANTIBIOTIKA PASIEN PNEUMONIA ANAK DI RS. PKU MUHAMMADIYAH YOGYAKARTA DENGAN METODE DEFINED DAILY DOSE (DDD) - Andriana Sari; Indah Safitri (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2016)
Pneumonia is one of respiratory tract infections disease which often occur. Treatment of pneumonia commonly based on empiric therapy is the use of broad spectrum antibiotic. The high consumption of antibiotic contributes on antimicrobial resistance. This research aims to acknowledge quantity of antibiotic and kinds of antibiotics with Defined Daily Dose (DDD) method RS PKU Muhammadiyah Yogyakarta during January to December 2014 This study used of observational research using collection retrospective data based on medical record on 2014. The study had 87 children pneumonia patients who fulfilled the criteria of inclusion and exclusion. The result showed there are 11 kinds of antibiotics. Total value of DDD/100 patientdays of those antibiotics is 24,51. The third highest quantity of antibiotics are Cefotaxime 14,64 DDD/100 patient-days, Ampicillin 4,06 DDD/100 patient-days, Ceftazidime 1,84 DDD/100 patient-days during January to December 2014. Based on calculation quantity of antibiotics the most used antibiotic on children pneumonia patients in RS PKU Muhammadiyah Yogyakarta period from January to December 2014 was cefotaxime 14,64 DDD / 100 patient-days.